Glyptothorax radiolus, a new species of sisorid catfish (Osteichthyes: Siluriformes) from northeastern India, with a redescription of G. striatus McClelland 1842 - Ng, Heok Hee; Lalramliana (Zootaxa, 2013)
Glyptothorax radiolus, new species, is described from the Brahmaputra River drainage in West Bengal, northeast India. It differs from most congeners in the Indian subcontinent in possessing plicae on the ventral surfaces of the pectoral spine and first pelvic-fin ray. The following combination of characters serve to distinguish it from congeners in the Indian sub-continent with plicate ventral surfaces of the pectoral spine and first pelvic-fin ray: eye diameter 6.6–7.4% HL interorbital distance 28.3–28.7% HL, head length 23.7–24.3% SL, wedge-shaped central depression in throracic adhesive apparatus devoid of skin ridges, unculiferous ridges of thoracic adhesive apparatus not extending anteriorly onto gular region, pec-toral fin length 21.4–22.8% SL, dorsal-fin spine length 11.6–13.9% SL, dorsal-to-adipose distance 26.6–26.8% SL, body depth at anus 11.2–11.4% SL, pelvic fin length 16.5–18.3% SL, adipose-fin base length 13.1–14.3% SL, anal-fin base length 13.4–14.0% SL, caudal peduncle length 20.9% SL, caudal peduncle depth 7.7% SL (1.4–1.5 times in body depth at anus), absence of distinct pale midlateral stripe on body, and 36 total vertebrae. Glyptothorax striatus, the type species of the genus, is also rediagnosed and redescribed in this study.